Living History: Historic Food - Campbell-Jewett , Madeleine (Petits Propos Culinaires, 2025)
Reconstruction of historic events, environments and episodes is a stupendously popular pastime almost everywhere. Visitors to Williamsburg will know also that it is deadly serious: no mere opportunity to dress up in armour and hit your neighbour over the head. The crafts and skills mobilized are equally impressive: Peter Brears and Ivan Day and their reconstructionist cookery, John Hudson and his wonderful English pottery - each of you may have a favourite. Here, the accent is on cookery.